Longitudinal assessment of white matter abnormalities following sports‐related concussion. Issue 2 (10th December 2015) - Meier, Timothy B.; Bergamino, Maurizio; Bellgowan, Patrick S. F.; Teague, T. K.; Ling, Josef M.; Jeromin, Andreas; Mayer, Andrew R.
Abstract: There is great interest in developing physiological‐based biomarkers such as diffusion tensor imaging to aid in the management of concussion, which is currently entirely dependent on clinical judgment. However, the time course for recovery of white matter abnormalities following sports‐related concussion (SRC) is unknown. We collected diffusion tensor imaging and behavioral data in forty concussed collegiate athletes on average 1.64 days (T1; n = 33), 8.33 days (T2; n = 30), and 32.15 days post‐concussion (T3; n = 26), with healthy collegiate contact‐sport athletes (HA) serving as controls ( n = 46). We hypothesized that fractional anisotropy (FA) would be increased acutely and partially recovered by one month post‐concussion. Mood symptoms were assessed using structured interviews. FA differences were assessed using both traditional and subject‐specific analyses. An exploratory analysis of tau plasma levels was conducted in a subset of participants. Results indicated that mood symptoms improved over time post‐concussion, but remained elevated at T3 relative to HA. Across both group and subject‐specific analyses, concussed athletes exhibited increased FA in several white matter tracts at each visit post‐concussion with no longitudinal evidence of recovery. Increased FA at T1 and T3 was significantly associated with an independent, real‐world outcome measure for return‐to‐play. Finally, we observed a nonsignificant trend for reduced tau in plasma of concussed athletes at T1 relative to HA, with tau significantly increasing by T2. These results suggest white matter abnormalities following SRC may persist beyond one month and have potential as an objective biomarker for concussion outcome. Hum Brain Mapp 37:833–845, 2016 . ©2015 Wiley Periodicals, Inc.